A Study to Evaluate the Effectiveness of the Instructional Program of the Swine Flu Program for High School Students in Selected Schools - Najjar, Yusra Al; Sidhu, Brahmaleen Kaur (Journal of Research in Vocational Education, 2025)
Communicable diseases are illnesses transmitted from an infectious agent to susceptible hosts, either directly or indirectly through intermediaries like vectors or the environment. In our country, diseases such as typhoid, cholera, malaria, chickenpox, and tuberculosis remain prevalent, alongside emerging threats like chikungunya, dengue, and H1N1 influenza. This study evaluates the impact of a planned teaching program on the knowledge of swine flu among high school students. A quasi-experimental design was utilized, involving a pre-test, the implementation of a teaching program, and a post-test conducted on the eighth day following the intervention. Sampling Sixty high school students were randomly selected for the study. A structured questionnaire was developed to assess students' knowledge about swine flu. Demographic analysis showed that 41.7% of participants were 14 years old, with an equal distribution of male and female students (50% each). Most students were Hindu (73.3%), lived in rural areas (58.3%), and resided in nuclear families (73.3%). None had been vaccinated against swine flu, and 31.7% received information about it from family members. The mean knowledge score improved from 53.12% in the pre-test to 77.75% in the post-test. Mean scores increased from 21.25 to 31.10. Statistical analysis using the Paired-‘t' test confirmed significant knowledge gains (p < 0.05). Chi-square tests showed no significant associations between demographic variables and mean knowledge scores, except for gender in the pre-test and religion in the post-test. The study demonstrates that the planned teaching program significantly enhanced students' knowledge of H1N1 (swine flu), underscoring its effectiveness in educational interventions.